Polycyclic aromatic compounds as anticancer agents: synthesis and biological evaluation of methoxy dibenzofluorene derivatives - Becker, Frederick F.; Banik, Bimal K. (Frontiers in Chemistry, 2014)
Synthesis of a new methoxy dibenzofluorene through alkylation, cyclodehydration and aromatization in a one-pot operation is achieved for the first time. Using this hydrocarbon, a few derivatives are prepared through aromatic nitration, catalytic hydrogenation, coupling reaction with a side chain and reduction. The benzylic position of this hydrocarbon with the side chain is oxidized and reduced. Some of these derivatives have demonstrated excellent antitumor activities in vitro. This study confirms antitumor activity depends on the structures of the molecules.